Fine structure of the eggshell of the blow fly, Lucilia cuprina. - Sukontason K.L. (2014)
The fine structure of the eggshell of blow fly, Lucilia cuprina (Wiedemann) (Diptera: Calliphoridae), was examined using scanning and transmission electron microscopy. Eggs, 1.09+/-0.07 mm in length and 0.25+/-0.05 mm in width, bore a relatively wide plastron that extending along almost the entire length. The polygonal pattern of chorionic sculpture was indistinct. The ultrathin section indicated a multi-layered eggshell having an exochorion, outer endochorion, pillars, an inner endochorion, innermost chorionic layer, and a wax layer. This study provides new information about the fine morphology of blow flies eggs. A key to differentiate the eggs of forensically important flies in Thailand is given.